H/W optimization for AIX test suite using PowerVC based Auto-Provisioning - Yajurvedi, Pavan G; R.Hulipalled, Dr. Vishwanath (IJRDO -Journal of Computer Science Engineering, 2021)
AIX regression test suite execution will take place on every weekly build, and this requires one or more lpars with pre-defined configurations need to be dedicated per job( eg: for specific function/feature/area). and each lpar needs a NIM installation.This model has a limitation of most of the H/W remains unutilized till next execution starts (due to dedicated H/W per job) and reconfigurations to improve utilization involves admin efforts.To address this limitation, we are going with new approach where Lpar/VMs will be created with required config on demand when there is a requirement, and it will be recycled (Memory, CPU, and Disks) immediately once the work is done in automated way with the help of PowerVC